Вы находитесь на странице: 1из 2

# 1

## For a fluid of constant density ρ, the acceleration curl is zero:

 
Du
∇× = 0. (0.1)
Dt
We’ll now evaluate the vertical component of the above equation, i.e.
   
∂ Dv ∂ Du
− = 0. (0.2)
∂x Dt ∂y Dt
We first expand out the material derivative to get
   
∂ ∂v ∂ ∂u
+ u · (∇v) − + u · (∇u) = 0 . (0.3)
∂x ∂t ∂y ∂t
We note that operators like ∂/∂t, ∂/∂x, ∂/∂y, ∂/∂z and ∇ all commute, i.e. their order
can be exchanged. Hence, recognising
∂v ∂u
ζ= − (0.4)
∂x ∂y
as the z component of the vorticity ω, we have
∂ζ ∂ ∂
+ [u · (∇v)] − [u · (∇u)] = 0 . (0.5)
∂t ∂x ∂y
Now using
∂ ∂F ∂G
[F · G] = ·G+F · (0.6)
∂x ∂x ∂x
for any two vector fields F and G, we have
∂ζ ∂u ∂(∇v) ∂u ∂(∇u)
+ · (∇v) + u · − · (∇u) − u · = 0. (0.7)
∂t ∂x ∂x ∂y ∂y
Commuting the operators ∂/∂x and ∇, as well as ∂/∂y and ∇, we have
   
∂ζ ∂v ∂u ∂u ∂u
+u·∇ + · (∇v) − u · ∇ − · (∇u) = 0 (0.8)
∂t ∂x ∂x ∂y ∂y
or, using Eq. 0.4,
∂ζ ∂u ∂u
+ u · ∇ζ + · (∇v) − · (∇u) = 0 (0.9)
∂t ∂x ∂y
and using the definition of the material derivative, this becomes
Dζ ∂u ∂u
+ · (∇v) − · (∇u) = 0 . (0.10)
Dt ∂x ∂y
Let’s now write out the remaining terms in component form:
       
Dζ ∂u ∂v ∂w ∂v ∂v ∂v ∂u ∂v ∂w ∂u ∂u ∂u
+ , , · , , − , , · , , =0 (0.11)
Dt ∂x ∂x ∂x ∂x ∂y ∂z ∂y ∂y ∂y ∂x ∂y ∂z
and after performing the dot products,
Dζ ∂u ∂v ∂v ∂v ∂w ∂v ∂u ∂u ∂v ∂u ∂w ∂u
+ + + − − − = 0. (0.12)
Dt ∂x ∂x ∂x ∂y ∂x ∂z ∂y ∂x ∂y ∂y ∂y ∂z
2
Grouping the second and third terms, as well as the fifth and sixth terms, we have
   
Dζ ∂u ∂v ∂v ∂u ∂v ∂u ∂w ∂v ∂w ∂u
+ + − + + − = 0. (0.13)
Dt ∂x ∂y ∂x ∂x ∂y ∂y ∂x ∂z ∂y ∂z
But incompressibility ∇ · u = 0 implies
∂u ∂v ∂w
+ =− (0.14)
∂x ∂y ∂z
and this term is seen to multiply ζ, from Eq. 0.4:
Dζ ∂w ∂w ∂v ∂w ∂u
− ζ+ − = 0. (0.15)
Dt ∂z ∂x ∂z ∂y ∂z
The final step is to make use of the x and y components of the vorticity ω:
∂w ∂v ∂u ∂w
ξ= − ; η= − (0.16)
∂y ∂z ∂z ∂x
which can be turned around to give expressions for the “vertical shear”
∂v ∂w ∂u ∂w
= −ξ ; = +η. (0.17)
∂z ∂y ∂z ∂x
Inserting these into Eq. 0.15, we have
   
Dζ ∂w ∂w ∂w ∂w ∂w
− ζ+ −ξ − + η = 0. (0.18)
Dt ∂z ∂x ∂y ∂y ∂x
The horizontal derivatives of w cancel, leaving
Dζ ∂w ∂w ∂w
− ζ− ξ− η = 0. (0.19)
Dt ∂z ∂x ∂y
This may be re-arranged as
Dζ ∂w ∂w ∂w
=ξ +η +ζ (0.20)
Dt ∂x ∂y ∂z
or since ω = (ξ, η, ζ), we can use the vector form

= (ω · ∇)w (0.21)
Dt
This is the vertical component of the vorticity equation. To get the other components,
we just use symmetry: replace ζ by ξ and w by u to get the x component,

= (ω · ∇)u (0.22)
Dt
and replace ζ by η and w by v to get the y component,

= (ω · ∇)v (0.23)
Dt
All three components can be written as a single vector expression

= (ω · ∇)u (0.24)
Dt
known as the “vorticity equation”. The right hand side of this equation is called the
“stretching term”, and it is the only way vorticity can change following a fluid element
when the density is constant.